Humans. Season 2.0 [videorecording (DVD)] - Allman, Marshall; Berrington, Emily; Bradley, Ruth, 1987- (Acorn, 2016)
Months after saying goodbye to sentient synth Mia and her family, the Hawkinses search for some semblance of normalcy. But when Niska arrives at their home unannounced, the family is pulled back into the dangerous lives of the synths.